p47phox-Dependent Oxidant Signalling through ASK1, MKK3/6 and MAPKs in Angiotensin II-Induced Cardiac Hypertrophy and Apoptosis - Fangfei Liu; Lampson M. Fan; Li Geng; Jian-Mei Li (MDPI AG, 2021)
The p47phox is a key regulatory subunit of Nox2-containing NADPH oxidase (Nox2) that by generating reactive oxygen species (ROS) plays an important role in Angiotensin II (AngII)-induced cardiac hypertrophy and heart failure. However, the signalling pathways of p47phox in the heart remains unclear. In this study, we used wild-type (WT) and p47phox knockout (KO) mice (C57BL/6, male, 7-month-old, n = 9) to investigate p47phox-dependent oxidant-signalling in AngII infusion (0.8 mg/kg/day, 14 days)-induced cardiac hypertrophy and cardiomyocyte apoptosis. AngII infusion resulted in remarkable high blood pressure and cardiac hypertrophy in WT mice. However, these AngII-induced pathological changes were significantly reduced in p47phox KO mice. In WT hearts, AngII infusion increased significantly the levels of superoxide production, the expressions of Nox subunits, the expression of PKCα and C-Src and the activation of ASK1 (apoptosis signal-regulating kinase 1), MKK3/6, ERK1/2, p38 MAPK and JNK signalling pathways together with an elevated expression of apoptotic markers, i.e., γH2AX and p53 in the cardiomyocytes. However, in the absence of p47phox, although PKCα expression was increased in the hearts after AngII infusion, there was no significant activation of ASK1, MKK3/6 and MAPKs signalling pathways and no increase in apoptosis biomarker expression in cardiomyocytes. In conclusion, p47phox-dependent redox-signalling through ASK1, MKK3/6 and MAPKs plays a crucial role in AngII-induced cardiac hypertrophy and cardiomyocyte apoptosis.